CDK1-driven phosphorylation networks promote glioblastoma progression via MAP1B-mediated microtubule destabilization - Li, Jun-Tao; Li, Meng-Da; Guo, Yong-Ji; Li, Zhi-Xiao; Qian, Rong-Jun; Ma, Chun-Xiao (Frontiers in Oncology, 2026)
BackgroundGlioblastoma (GBM) is the most aggressive and prevalent malignant brain tumor in adults, with poor prognosis despite current therapies. Cyclin-dependent kinase 1 (CDK1), a master regulator of cell cycle progression, has been implicated in oncogenesis, but its downstream phosphorylation network in GBM remains incompletely defined.MethodsCDK1 expression was examined in clinical GBM tissues and cell lines. Functional studies were performed in U251 cells using CDK1-specific shRNAs. Label-free phosphoproteomic profiling and bioinformatics analyses were conducted to map CDK1-regulated signaling pathways and substrates. Prognostic associations were evaluated using Clinical Proteomic Tumor Analysis Consortium (CPTAC) datasets, and functional assays were used to validate candidate substrates.ResultsCDK1 was significantly upregulated in GBM tissues, and its knockdown suppressed proliferation, migration, and invasion of U251 cells. Phosphoproteomic analysis identified 15,156 phosphorylation sites, of which 2,836 were significantly altered by CDK1 inhibition, implicating pathways related to cell cycle regulation, DNA replication, and DNA damage repair. Subcellular localization revealed nuclear enrichment, including phosphorylation changes in RB1 and TP53. Importantly, CDK1-mediated hyperphosphorylation of microtubule-associated protein 1B (MAP1B) at multiple residues (Ser832, Ser1260, Ser1899, Ser1939, Ser2209, Ser2271) correlated with poor prognosis and promoted microtubule destabilization. Functional assays confirmed that MAP1B knockdown impaired GBM cell growth, migration, and invasion.ConclusionThis study demonstrates that CDK1 is a critical oncogenic driver in GBM, regulating broad phosphosignaling networks and promoting tumor progression via MAP1B-dependent microtubule destabilization. MAP1B phosphorylation emerges as a potential prognostic biomarker. These findings support the development of CDK1-targeted therapies, alone or combined with microtubule-stabilizing agents, for improved GBM management.